Molecular cloning, spatiotemporal and functional expression of GABA receptor subunits RDL1 and RDL2 of the rice stem borer Chilo suppressalis. (March 2018) - Sheng, Cheng-Wang; Jia, Zhong-Qiang; Ozoe, Yoshihisa; Huang, Qiu-Tang; Han, Zhao-Jun; Zhao, Chun-Qing
Abstract: Insect γ-aminobutyric acid (GABA) receptor (GABAR) is one of the major targets of insecticides. In the present study, cDNAs ( CsRDL1A and CsRDL2S ) encoding the two isoforms of RDL subunits were cloned from the rice stem borer Chilo suppressalis . Transcripts of both genes demonstrated similar expression patterns in different tissues and developmental stages, although CsRDL2S was ∼2-fold more abundant than CsRDL1A throughout all development stages. To investigate the function of channels formed by Cs RDL subunits, both genes were expressed in Xenopus laevis oocytes singly or in combination in different ratios. Electrophysiological results using a two-electrode voltage clamp demonstrated that GABA activated currents in oocytes injected with both cRNAs. The EC50 value of GABA in activating currents was smaller in oocytes co-injected with CsRDL1A and CsRDL2S than in oocytes injected singly. The IC50 value of the insecticide fluralaner in inhibiting GABA responses was smaller in oocytes co-injected with different cRNAs than in oocytes injected singly. Co-injection also changed the potency of the insecticide dieldrin in oocytes injected singly. These findings suggested that heteromeric GABARs were formed by the co-injections of CsRDL1A and CsRDL2S in oocytes. Although the presence of Ser at the 2′-position in the second transmembrane segment was responsible for the insensitivity of GABARs to dieldrin, this amino acid did not affect the potencies of the insecticides fipronil and fluralaner. These results lead us to hypothesize that C. suppressalis may adapt to insecticide pressure by regulating the expression levels of CsRDL1A and CsRDL2S and the composition of both subunits in GABARs. Graphical abstract: Image 1 Highlights: cDNAs encoding GABAR subunits ( CsRDL1A and CsRDL2S ) were cloned from Chilo suppressalis. Spatiotemporal expression levels of CsRDL1A and CsRDL2S mRNAs were similar in C. suppressalis body tissues. Cs RDL1A and 2S channels demonstrated distinct pharmacological profiles when expressed in combination. Generation of heteromers may be associated with adaptation to insecticide pressure.